Metastable states in terminal orientation of hinged symmetric bodies in a flow. (February 2017) - Castillo, D.; Chung, B.; Schnitzer, K.; Soriano, K.; Su, H.; Vaidya, A.
Abstract: Symmetric bodies such as cylinders and spheroidal bodies, in their terminal stable states, are long known to have their long axis align themselves perpendicular to the direction of the flow. This property has been confirmed in primarily sedimentation based theoretical, experimental and numerical techniques and the transition to a terminal stable state is believed to coincide with the onset of significant inertial effects in the flow. However, the threshold at which this transition occurs is yet unknown. We conduct modified experiments with hinged bodies and a CFD study to examine the nature of the transition of prolate spheroids and cylinders of various aspect ratios, from initial to their terminal stable equilibrium. Our experiments and numerics, both reveal the presence of intermediate metastable states which are sensitive to the flow Reynolds number and physical attributes of the immersed body and gradually lead to the stable state.